Appel à une action concertée pour lever les obstacles à l’emploi des Québécois d’expression dans la Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

New Report Calls for Coordinated Action to Tackle Employment Barriers Facing English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

Participation à la conférence de l’ACFAS sur les femmes officielles des communautés linguistiques minoritaires à Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Attending the ACFAS Official Women Minority Language Communities Conference in Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Caractéristiques sociodémographiques des minorités visibles - Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Gatineau.

Caractéristiques sociodémographiques des minorités visibles - Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Laval.

Caractéristiques sociodémographiques des minorités visibles - Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Longueil.

Caractéristiques sociodémographiques des minorités visibles - MRC L'Assomption - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC L'Assomption.

Caractéristiques sociodémographiques des minorités visibles - MRC La Vallée-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC La Vallée-du-Richelieu.

Caractéristiques sociodémographiques des minorités visibles - MRC Les Moulins - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Les Moulins.

Caractéristiques sociodémographiques des minorités visibles - MRC Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Roussillon.

Caractéristiques sociodémographiques des minorités visibles - MRC Thérèse-De Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Thérèse-De Blainville.

Caractéristiques sociodémographiques des minorités visibles - MRC Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Vaudreuil-Soulanges.

Caractéristiques sociodémographiques des minorités visibles - Reste du Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques pour la province de Québec et ses régions RTS.

Caractéristiques sociodémographiques des minorités visibles - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de Chaudière-Appalaches

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Abitibi-Témiscamingue.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Est-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Estrie – CHU de Sherbrooke.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Ouest-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de l'Outaouais.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Capitale-Nationale

Caractéristiques sociodémographiques des minorités visibles - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Mauricie-et-du-Centre-du-Québec.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Centre.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Est.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Ouest.

Caractéristiques sociodémographiques des minorités visibles - RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de Lanaudière.

Caractéristiques sociodémographiques des minorités visibles - RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de Laval.

Caractéristiques sociodémographiques des minorités visibles - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS des Laurentides.

Caractéristiques sociodémographiques des minorités visibles - RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Bas-Saint-Laurent.

Caractéristiques sociodémographiques des minorités visibles - RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Centre-Ouest-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Centre-Sud-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Nord-de-l'Île-de-Montréal.

Caractéristiques sociodémographiques des minorités visibles - RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS du Saguenay-Lac-Saint-Jean

Caractéristiques sociodémographiques des minorités visibles - Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Sherbrooke.

Caractéristiques sociodémographiques des minorités visibles - Ville de Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de Québec.

Socio-Demographic Profile of Québec's English-speaking Youth Aged 15-29 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This report profiles the situation of English-speaking citizens of Québec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood. Youth is a stage of life characterized by challenges that can be decisive in the quality of life of individuals and their communities and for most Québecers aged 15-29, these milestones are: completing school, gaining occupational experience and even starting a family and establishing a household. This report offers current information organized to support “the village” - from policymakers and program managers to public institutions, community organizations and networks - whose actions impact the lives of minority language youth striving to build their future and the future of all Québec’s citizens.

Caractéristiques sociodémographiques des minorités visibles au Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques pour la province de Québec et ses régions RTS.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2024)

Socio-Demographic Characteristics of Visible Minorities in Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Gatineau, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Laval, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Longueil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Longueil, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in MRC de L'Assomption - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de L'Assomption.

Socio-Demographic Characteristics of Visible Minorities in MRC de La Vallée-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de La Vallée-du-Richelieu.

Socio-Demographic Characteristics of Visible Minorities in MRC de Les Moulins - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Les Moulins.

Socio-Demographic Characteristics of Visible Minorities in MRC de Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Roussillon.

Socio-Demographic Characteristics of Visible Minorities in MRC de Thérèse-De Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Thérèse-De Blainville.

Socio-Demographic Characteristics of Visible Minorities in MRC de Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Vaudreuil-Soulanges.

Socio-Demographic Characteristics of Visible Minorities in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec.

Socio-Demographic Characteristics of Visible Minorities in Québec City - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec City, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for the rest of Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Chaudière-Appalaches.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Abitibi-Témiscamingue.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Est-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Estrie – CHU de Sherbrooke.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de l'Outaouais.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Capitale-Nationale.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Mauricie-et-du-Centre-du-Québec.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Centre.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Est.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Ouest.

Socio-Demographic Characteristics of Visible Minorities in RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Lanaudière.

Socio-Demographic Characteristics of Visible Minorities in RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de Laval.

Socio-Demographic Characteristics of Visible Minorities in RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS des Laurentides.

Socio-Demographic Characteristics of Visible Minorities in RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Bas-Saint-Laurent.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Ouest-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Centre-Sud-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Nord-de-l'Île-de-Montréal.

Socio-Demographic Characteristics of Visible Minorities in RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS du Saguenay - Lac-Saint-Jean

Socio-Demographic Characteristics of Visible Minorities in Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Sherbrooke, which is considered a territory equivalent to an MRC.

Nord-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Nord-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Chaudière-Appalaches - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Abitibi-Témiscamingue - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Abitibi-Témiscamingue - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Est-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Estrie – CHU de Sherbrooke - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Estrie – CHU de Sherbrooke - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Ouest-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Outaouais - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de l'Outaouais - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Côte-Nord - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Gaspésie - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Centre - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Montérégie-Est - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Lanaudière - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Lanaudière - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Laval - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de Laval - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Îles - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Îles - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Laurentides - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS des Laurentides - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Bas-Saint-Laurent - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Bas-Saint-Laurent - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Nord-de-l'Île-de-Montréal - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Saguenay – Lac-Saint-Jean - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS du Saguenay – Lac-Saint-Jean - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Employment Situation of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2024)

Pre-Budget Submission 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
The Provincial Employment Roundtable Table (PERT) is pleased to submit this brief and proposition to the Ministry of Finance’s 2024-25 Pre-budget consultations. Founded in 2020, PERT is a non-profit organization focused on addressing the employment and employability issues that are being faced by Québec’s English-speaking communities. Since its creation, PERT has become the leading voice on the solutions to English speakers’ employment challenges. Through its research and stakeholder coordination work, PERT has published over 25 reports that capture the employment issues and needs of English speakers across all 17 regions of the province and has established a membership of 90 employment service deliverers, educational institutions, regional organizations, and employers. The employment situation of Québec’s English-speaking population continues to worsen, as demonstrated by the higher unemployment rates and French-language barriers that English speakers face in Québec’s labour market. In this brief, we identify two key contributors to the continued employment challenges of English speakers: a lack of targeted employment services and programs for English speakers and a lack of work-integrated French language training programs to help them enter and remain in the labour market. English speakers’ employment and economic challenges are part of the larger economic headwinds that are facing Québec, which include unprecedented labour shortages, demographic decline, and problems with attracting and retaining talent. This mémoire summarizes PERT’s research findings, particularly the employment challenges facing the English-speaking community in Québec, and advances recommendations for the next budget that will address these challenges and help create a more productive, inclusive, and prosperous Québec for all.

Propositions prébudgétaire 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
La Table ronde provinciale de l'emploi (PERT) a le plaisir de soumettre ce mémoire et proposition aux consultations prébudgétaires 2024-25 du ministère des Finances. Fondée en 2020, PERT est une organisation à but non lucratif qui se consacre aux problèmes d'emploi et d'employabilité auxquels sont confrontées les communautés d’expression anglaise du Québec. Depuis sa création, PERT est devenu le principal porte-parole des solutions aux problèmes d'emploi des Québécois d’expression anglaise. Grâce à son travail de recherche et de coordination des parties prenantes, PERT a publié plus de 25 rapports qui décrivent les problèmes et les besoins des Québécois d’expression anglaise en matière d'emploi dans les 17 régions de la province. PERT compte parmi ses plus de 90 membres des prestataires de services d'emploi, des établissements d'enseignement, et des organisations régionales et employeurs. La situation d'emploi de la population d’expression anglaise du Québec continue de se détériorer, comme en témoignent les taux de chômage plus élevés et les obstacles liés à la langue française auxquels les Québécois d’expression anglaise sont confrontés sur le marché du travail québécois. Dans ce mémoire, nous identifions deux facteurs clés qui contribuent aux défis continus des Québécois d’expression anglaise en matière d'emploi : le manque de services et de programmes d'emploi ciblés pour les Québécois d’expression anglaise et le manque de programmes de formation en français intégrés au travail pour les aider à entrer sur le marché du travail et à y rester. Les difficultés économiques et d'emploi des Québécois d’expression anglaise s'inscrivent dans le contexte plus large des vents contraires auxquels le Québec est confronté, notamment les pénuries de main-d'oeuvre sans précédent, le déclin démographique et les problèmes liés à l'attraction et à la rétention des talents. Ce mémoire résume les résultats de la recherche de PERT, en particulier les défis en matière d'emploi auxquels est confrontée la communauté d’expression anglaise du Québec, et propose des recommandations pour le prochain budget qui permettront de relever ces défis et de créer un Québec plus productif, plus inclusif et plus prospère pour tous.

Situation d’emploi des personnes d'expression anglaise au Québec - Provincial Employment Roundtable (PERT) (2024)

Exploring the English-speaking Landscape : A Typology of Vulnerability Associated with Employment in Quebec's English-speaking Population - Warnke, Jan; Bolger, Laura-Lee (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This exploratory study uses geodemographic analytical methods to investigate the English-speaking population of Quebec, with a specific focus on vulnerability indicators associated with employment and their spatial distribution within the province. Using Ward’s cluster analysis method, eight distinct groups were identified and mapped, each showcasing unique characteristics that warrant tailored policy measures to effectively tackle regional employment challenges. Future research should delve into the differential impacts of various variables across clusters, particularly those related to mobility and aboriginal identity, thereby facilitating the derivation of targeted policy interventions.

Socio-demographic Profile of the Population Aged 55 and Over : Province of Quebec - Pocock, Joanne (2023)

Press Release: New study reveals economic precarity and limit job supports for racialized communities and English-speaking immigrants in Québec. - Provincial Employment Roundtable (PERT) (2023)

Une nouvelle étude révèle la précarité économique et l’insuffisance des aides à l’emploi pour les communautés racialisées et les immigrants d’expression anglaise au Québec - Provincial Employment Roundtable (PERT) (2023)

August & September 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

Economic Development and Community Vitality : A Report on Federal Funding Streams Available to the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Youth Employment Services (YES) (2023)
The following report provides an overview of the main federal funding streams for the English-speaking community in Quebec (ESCQ) along with the French-speaking community in the rest of Canada. This includes an overview and analysis of the Canada Economic Development for Quebec Regions (CED-Q), including the Official Languages Economic Development Initiative (EDI) and other official language minority communities (OLMCs) specific funding streams: Regional Economic Growth through Innovation (REGI), the Quebec Economic Development Program (QEDP), and the Community Futures Program (CFP). As a means of comparing funding levels for the French-speaking community outside of Quebec, this study also reviews Canada Economic Development for the Rest of Canada (CED-ROC).
Keywords: Official Language Minority Community (OLMC)

Mapping Employment Supports for Québec's Racialized and Immigrant English-speaking Communities - Gagnon, Morgan; Kuzviwanza, Sta (Provincial Employment Roundtable (PERT), 2023)

June & July 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)

Provincial Employment Roundtable : Québec and the rest: A survey of national and international approaches to adult language training - Kuzviwanza, Sithandazile; Holt, Cimminnee (Provincial Employment Roundtable (PERT), 2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)

February & March 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)

Employment Services - Assistance and Referral Centre (ARC) (2023)

Demographic Profiles of Québec's English-speaking Communities, Quebec - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Chaudière-Appalaches - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de l'Outaouais - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Capitale-Nationale - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Gaspésie - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Montérégie-Ouest - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Lanaudière - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de Laval - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS des Îles - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS des Laurentides - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2021-2022 - Provincial Employment Roundtable (PERT) (2023)

Annual Report 2022-2023 - Provincial Employment Roundtable (PERT) (2023)

Mémoire : Réflexion sur l'avenir de la langue française - Provincial Employment Roundtable (PERT) (2023)

Strategic Plan 2024-2027 : The Way Forward - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is a non-profit multi-stakeholder initiative focused on addressing the employment and employability challenges facing Québec’s English-speaking community. This strategic plan for 2024-2027 outlines five key shifts, the introduction of a third organisational pillar, and eleven strategic goals that will guide PERT’s efforts to address the unique employment challenges faced by English speakers in Québec.

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

Enquête de 2021 sur l’emploi auprès des Québécois(es) et des organisations d’expression anglaise - Provincial Employment Roundtable (PERT) (2022)
Le présent rapport expose les expériences des Québécois·e·s d’expression anglaise dans la province au regard de l’emploi ainsi que les différents enjeux rencontrés et les besoins éprouvés par cette population sur le marché du travail. Désignée « communauté linguistique minoritaire officielle » du Québec, la population québécoise d’expression anglaise est toutefois caractérisée par une réelle diversité identitaire, comportant ainsi une pluralité de sous-communautés qui ne connaissent pas toutes les mêmes défis. Des points de convergence néanmoins existent, notamment du point de vue du statut socioéconomique de la communauté d’expression anglaise prise dans son ensemble. De fait, en dépit du statut d’élite socioéconomique qu’occupaient historiquement les personnes d’expression anglaise au Québec, la communauté actuelle est dans son ensemble caractérisée, en comparaison d’avec la majorité linguistique d’expression française, par des taux élevés de chômage et de plus faibles revenus. Ce rapport s’appuie des données provenant d’une enquête réalisée en deux volets. Le premier volet consistait à sonder 259 Québécois·e·s d’expression anglaise à propos de leur relation au marché du travail, de leur niveau de français, des répercussions de la pandémie et des obstacles à leur accès au marché du travail. À cette première enquête venait s’ajouter une seconde s’intéressant aux points de vue de 29 organisations qui emploient des personnes d’expression anglaise et servent leurs intérêts, quant au paysage de l’emploi pour cette population, et aux effets sur l’emploi des politiques linguistiques promouvant le français.

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

September 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

L'étude éducation à l'emplois (E2E) - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
Au Québec, la communauté noire et la communauté d'expression anglaise occupent toutes deux des positions relativement précaires sur le plan économique et de l'emploi : toutes deux connaissent des taux de chômage supérieurs à la moyenne et gagnent des revenus médians après impôt inférieurs à ceux de la population totale de la province. La communauté noire d'expression anglaise (CNEA) se trouve à l'intersection de ces deux communautés et subit la double marginalisation d'être à la fois une minorité raciale et linguistique au Québec.

The Education to Employability Study - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
In Québec, both the Black community and the English-speaking community occupy relatively precarious economic and employment positions: both experience higher-thanaverage unemployment rates and earn lower median after-tax incomes compared to the province’s total population. The English-speaking Black Community (ESBC) sits at the intersection of these two communities, and experiences the double marginalization of being both a racial and linguistic minority in Québec.

List of Employers in Quebec City Region with Jobs That Require English Skills - Voice of English-speaking Quebec (VEQ) (2022)

March 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

French-Language Training for the Workforce : A review of French-language training programs for the workforce in Québec - Provincial Employment Roundtable (PERT) (2022)
This report examines the status of French-language workforce programs (FLWPs) in Québec. FLWPs consist of language learning that is specifically designed to increase the integration of workers into the labour market by focusing on the vocabulary and language skills they need to improve their employability. In this report, we conducted an inventory of FLWPs that are available to French-language learners and identified the key needs, gaps and areas for improvement in the ecosystem.

Programmes de francisation de la main-d'oeuvre au Québec : Évaluation des programmes de francisation de la main-d'oeuvre québécoise - Provincial Employment Roundtable (PERT) (2022)
Le présent rapport se penche sur l’état des programmes de francisation pour la main-d’oeuvre (PFMO) au Québec. Les PFMO sont des cours de français spécifiquement conçus pour accroître l’intégration des apprenantes et apprenants de langues sur le marché du travail en étant axés sur le vocabulaire et les compétences linguistiques qui contribuent à leur employabilité. Dans ce rapport nous avons recensé les PFMO offerts aux apprenantes et apprenants de langue française, et relevé les besoins clés, les lacunes et les possibilités d’amélioration au sein de l’écosystème.

Showing up when it counts : 2021 Annual report - Youth Employment Services (YES) (2022)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2022)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

Nord-du-Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Chaudière-Appalaches - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Abitibi-Témiscamingue - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Est-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Estrie – CHU de Sherbrooke - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de l'Outaouais - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Capitale-Nationale - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Côte-Nord - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Gaspésie - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Centre - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Est - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Ouest - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Lanaudière - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS de Laval - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS des Îles - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS des Laurentides - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Bas-Saint-Laurent - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Ouest-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Centre-Sud-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Nord-de-l'Île-de-Montréal - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

RTS du Saguenay – Lac-Saint-Jean - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Black in Quebec - Davids, John; Fang, Xiaoyan; Bramble, Shania (2021)

2nd Annual General Meeting 2020-2021 - Regional Development Network (RDN) (2021)

Annual Report 2020-2021 - Regional Development Network (RDN) (2021)

East Island Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Annual Report 2020-2021 - Youth Employment Services (YES) (2021)
As a not-for-profit organization, YES enriches the community by providing English-language support services to help Quebecers find employment and start and grow businesses. YES Employment + Entrepreneurship has been broadening access to opportunities for Quebec’s English-speaking community for over 25 years now. As we reflect on the organization’s 25th anniversary in the midst of the pandemic, we are reminded of the vital importance of our career and business support services.

Rapport annuel 2020-2021 - Youth Employment Services (YES) (2021)
En qualité d’organisme sans but lucratif, YES contribue à l’enrichissement de la communauté en offrant des services de soutien en anglais pour aider les québécois à trouver un emploi ou démarrer ou développer leurs entreprises. Depuis plus de 25 ans, YES Emploi + Entrepreneuriat facilite l’accès à différentes opportunités de croissance auprès de la communauté d’expression anglaise du Québec. Célébrer le 25e anniversaire de notre organisation en pleine pandémie nous rappelle à quel point nos services d’accompagnement à l’emploi et d’aide aux entreprises sont d’une importance vitale.

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)

Newsletter - Coasters Association (2020)

Black in Quebec : Progress Report - Davids, John; Fang, Xiaoyan (2020)

Profil de la jeunesse anglophone de la Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Ce profil de la situation de la jeunesse anglophone de la Gaspésie et des Îles-de-la-Madeleine a été commandité par trois organisations communautaires : le Comité pour l’action sociale anglophone (CASA), le Conseil des Madelinot·e·s anglophones (CAMI) et Vision Gaspé-Percé Now. Des travaux de recherche-action fondés sur une approche participative et communautaire ont servi de base au développement de ce profil. Ce faisant, l’étude sur laquelle le présent document se fonde permet d’avoir un portrait des réalités propres à la jeunesse, développé par les jeunes elleux-mêmes; ceci permettra de travailler plus efficacement à la résolution des enjeux et des difficultés auxquels ils et elles font face dans les différentes communautés de la région. Une méthode d’approche mixte a ainsi été développée via la combinaison d’une enquête en ligne et de groupes de discussions sur des sujets liés à l’émigration, à l’éducation, à l’emploi, à la vie sociale, aux services, etc. Au total, 438 jeunes de 15 à 35 ans ont participé à l’enquête en ligne, et neuf groupes de discussion ont été instaurés sur un total de six communautés regroupant 82 jeunes.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people aged 15-35 filled out the survey and nine focus groups were held in a total of six communities with a total of 82 youth.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Job Search in the Time of Covid-19 : Resource Guide for Job Seekers - Youth Employment Services (YES) (2020)

Profil des jeunes anglophones des Laurentides 15 à 29 ans - 4Korners (2020)
Selon les données publiées par l’Institut de la statistique du Québec en 2020, la population vivant dans les régions administratives de la province a considérablement changé de 2019 à 2021 en raison des répercussions sociales directes de la pandémie de COVID-19 et de ses conséquences sur la migration, la mobilité, l’attractivité de la main-d’oeuvre, la conciliation travail-famille, les habitudes de vie et les loisirs. Ainsi, on estime que 632 000 habitants vivaient dans la région des Laurentides au 1er juillet 2020, marquant une augmentation de 17,7 % pour l’année 2019-2020; ce pourcentage est plus élevé que le taux moyen de l’ensemble de la province (8,5 %) pour cette année. De fait, il est important de souligner que cette région présente la plus forte augmentation depuis le début de la pandémie en mars 2020.

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

Report on Youth Employability in the Greater Quebec City Region - Voice of English-speaking Quebec (VEQ) (2020)
In the winter of 2019-2020, we conducted a survey of English-speaking youth aged 15 to 29 as well as six focus groups at the English high schools in the region to support two projects related to youth employability. Through our needs analysis, we sought to evaluate youth knowledge and/or use of the services offered by the Carrefour jeunesse-emploi centres as well as to gain some insights into the postsecondary education and career plans of the students at the local English high schools. These results are meant to provide a snapshot of the perspectives of Englishspeaking youth on employment in the Greater Quebec City region at this time. Though small in scope and sample size (53 survey participants, 32 focus group participants), this study captures the very real hopes and frustrations of our minority population. At the same time, it also proposes some very concrete and achievable outcomes. We hope that this document can serve as a springboard for employers and service providers to work with us, and members of our community, to increase the employability of English-speaking youth in the Greater Quebec City region. Let’s build a better future for all Québécois.

Who We Are - Youth Employment Services (YES) (2020)